Functional diversity of Nocardia in metabolism. (28th August 2013) - Luo, Quan; Hiessl, Sebastian; Steinbüchel, Alexander
Summary Bacteria affiliated in the genus Nocardia are aerobic and Gram‐positive actinomycetes that are widely found in aquatic and terrestrial habitats. As occasional pathogens, several of them cause infection diseases called 'nocardiosis' affecting lungs, central nervous system, cutaneous tissues and others. In addition, members of the genus Nocardia exhibit an enormous metabolic versatility. On one side, many secondary metabolites have been isolated from members of this genus that exhibit various biological activities such as antimicrobial, antitumor, antioxidative and immunosuppressive activities. On the other side, many species are capable of degrading or converting aliphatic and aromatic toxic hydrocarbons, natural or synthetic polymers, and other widespread environmental pollutants. Because of these valuable properties and the application potential, Nocardia species have attracted much interest in academia and industry in recent years. A solid basis of genetic tools including a set of shuttle vectors and an efficient electroporation method for further genetic and metabolic engineering studies has been established to conduct efficient research. Associated with the increasing data of nocardial genome sequences, the functional diversity of Nocardia will be much faster and better understood.